Peran Pendidikan Karakter dalam Meningkatkan Pemahaman Terhadap Nilai-Nilai Islam - Naily Nur Fitri Amaliyah; Khotimah Suryani (AJER: Advanced Journal of Education and Religion, 2026)
Learning interest is a phenomenon that emerges from the interaction between individuals and their environment and plays a crucial role in supporting successful learning. However, a decline in students’ learning interest is still frequently observed at various levels of education, as reflected in low student engagement during the learning process, which may be caused by ineffective learning methods and strategies, less engaging learning media, and limited teacher innovation. The use of digital learning media such as Wordwall-based media can create a more enjoyable learning experience, increase student activity and engagement, and foster learning interest. This study aimed to determine the influence of using Wordwall-based learning media on students’ learning interest in Pancasila Education for Grade IV students at MI Tanwirul Ma’arif Takerharjo. The research employed a quantitative method with a one-group pretest–posttest design involving all Grade IV students as the research sample. Data were collected through questionnaires, observations, and interviews and analyzed using statistical and hypothesis testing. The results showed that the average students’ learning interest increased from 56.93 in the pretest to 66.78 in the posttest, with a significance value of 0.000 ≤ 0.05, indicating that the null hypothesis was rejected and the alternative hypothesis was accepted. These findings indicate that the use of Wordwall learning media has a significant effect on improving students’ learning interest by creating a more interactive and enjoyable learning atmosphere and can be considered an effective alternative in Pancasila Education learning.